The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/bc200362a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vivo Evaluation of the Biodistribution of a 18F-Labeled Conjugate Gold-Nanoparticle-Peptide with Potential Biomedical Application

Abstract: Gold nanoparticles (AuNPs) have been extensively used in biological applications because of their biocompatibility, size, and ease of characterization, as well as an extensive knowledge of their surface chemistry. These features make AuNPs readily exploitable for biomedical applications, including drug delivery and novel diagnostic and therapeutic approaches. In a previous work, we studied ex vivo distribution of the conjugate C(AuNP)-LPFFD for its potential uses in the treatment of Alzheimer's disease. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 38 publications
5
68
0
Order By: Relevance
“…In another study, Guerrero et al reported the radiolabeling of Au nanoparticles with 18 F for use as a PET radiotracer. 50 In this study, N-succinimidyl-4-[ 18 F]-fluorobenzoate was covalently linked to Au nanoparticles conjugated with amphipathic peptide, CLPFFD. In vivo PET imaging in rats after administration of the radiolabeled nanoparticles showed that they cleared through both hepatobiliary as well as renal route.…”
Section: Preclinical Studies With Radiolabeled Inorganic Nanoparticlesmentioning
confidence: 99%
“…In another study, Guerrero et al reported the radiolabeling of Au nanoparticles with 18 F for use as a PET radiotracer. 50 In this study, N-succinimidyl-4-[ 18 F]-fluorobenzoate was covalently linked to Au nanoparticles conjugated with amphipathic peptide, CLPFFD. In vivo PET imaging in rats after administration of the radiolabeled nanoparticles showed that they cleared through both hepatobiliary as well as renal route.…”
Section: Preclinical Studies With Radiolabeled Inorganic Nanoparticlesmentioning
confidence: 99%
“…Their in vivo biodistribution was assessed and high accumulation in the bladder and urine, and low intestinal uptake were demonstrated. Ex vivo biodistribution revealed accumulation in the RES organs which could be due to the negative surface charge of the nanoparticles, resulting in phagocytisis by macrophages of these organs [5]. A fast and simple strategy of radiolabeling and coating magnetic nanoparticles was introduced by Sun Z. et al (2016).…”
Section: Fluorine-18mentioning
confidence: 99%
“…126129 The utilization of 18 F-labeled gold nanoparticles for PET imaging was first reported by Guerrero et al, 130 in which the gold nanoparticles of ~12 nm were synthesized by citrate reduction of HAuCl 4 . The nanoparticles were functionalized with two different peptides, CK and CLPFFD, and 18 F-SFB was covalently bound to the nano-particle conjugate.…”
Section: Carriers For Pet Image-guided Drug Deliverymentioning
confidence: 99%